2021
DOI: 10.3389/fneur.2021.578446
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the Ballast Long Guiding Sheath for Neuroendovascular Procedures: Institutional Experience in 68 Cases

Abstract: Background: The rise of neurointerventional devices has created a demand for guide systems capable of navigating to the carotid artery consistently regardless of tortuosity. The shift toward large distal access catheters (DACs) and desire for greater trackability have inspired the creation of flexible, supportive, large-lumen long guiding sheaths. Recently, the Ballast long guiding sheath was introduced to provide stability and flexibility while navigating neurointerventional devices through tortuous intracran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For example, Hassan et al reported their experience using a 0.088″ ID AC in 73 patients, via both femoral and radial approaches, with a 100% technical success rate, but only a collective 8.8% of patients had any form of anatomic tortuosity. 8 Similarly, Lin et al reported use with another 0.088″ ID AC, via a femoral approach, with a 100% technical success rate, but only 12% of patients had significant cervical tortuosity. 9 In a cohort more similar to ours, Rinaldo et al reported the use of a 0.090″ ID AC in 154 patients, via a femoral approach, with a success rate of 98.1% and a combined rate of type II or III aortic arch of 37.3%.…”
Section: Discussionmentioning
confidence: 96%
“…For example, Hassan et al reported their experience using a 0.088″ ID AC in 73 patients, via both femoral and radial approaches, with a 100% technical success rate, but only a collective 8.8% of patients had any form of anatomic tortuosity. 8 Similarly, Lin et al reported use with another 0.088″ ID AC, via a femoral approach, with a 100% technical success rate, but only 12% of patients had significant cervical tortuosity. 9 In a cohort more similar to ours, Rinaldo et al reported the use of a 0.090″ ID AC in 154 patients, via a femoral approach, with a success rate of 98.1% and a combined rate of type II or III aortic arch of 37.3%.…”
Section: Discussionmentioning
confidence: 96%
“…8 9 Previous 0.088 inch guide catheters have been limited by their stability and trackability into the intracranial vasculature. [10][11][12][13][14] This limitation prevents distal placement and enhanced stability for the delivery of large neurointerventional devices. The TracStar Large Distal Platform (LDP) (Imperative Care, Campbell, California, USA) is the first ever supportive 0.088 inch guide catheter with a hyperflexible tip designed to track to the intracranial vasculature.…”
Section: Introductionmentioning
confidence: 99%